Effect of Lubricant Use on Cervicovaginal Cytology – What's the Evidence? - Santos, Diana Magalhães dos; Matos, Maria Beatriz Freire Oliveira Coelho de; Sousa, Ana Raquel Borges; Fertusinhos, Francisco Correia de Almeida; Pendás, Rosa Maria Couceiro (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2023)
Objective To determine if the use of lubricating gel on the speculum during the cervicovaginal cytology examination interferes with the results obtained, as well as whether it reduces reported discomfort in patients.Data sources A systematic review was carried out according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) recommendations, with a search in the Pubmed/Medline, Scielo, Cochrane Library, Embase databases of articles published between January 2011 and May 2022. The keywords used were cytology, speculum, lubricant, result, and pain.Selection of studies The initial search resulted in 306 articles, of which were excluded three because they were duplicates, 257 after reading the title and abstract and 41 after reading the full text. Thus, five articles were selected for the study: four randomized clinical trials and one metanalysis.Data collection The selection of articles was performed by two investigators. The 5 selected articles were read in full and submitted to a comparative analysis.Data synthesis Screening through cervicovaginal cytology allows for early diagnosis and reduction of associated mortality, but the procedure can be associated with pain. A small amount of aqueous lubricating gel in the speculum can be used to reduce the discomfort associated with performing cervicovaginal cytology.Conclusion The use of lubricating gel in the speculum does not seem to be associated with a change in the cytology result and reduces the discomfort associated with its insertion into the vagina.
Keywords: Cytology; Speculum; Lubricant; Result; Pain